The Origin of the Terms “Canaan”, “Phoenician” and “Purple” - Astour, Michael C.
*kina‛u, *kin‛anu “Occident”; Pûnî, gentilic of Puwwā; puwwā “red dye”; *prpr “boiling, decoction”; term for purple dye, obtained by prolonged boiling.